The Effect of Love of Money, Peer Group and Financial Literacy on Personal Financial Management in Management Study Program Students, Faculty of Economics and Business, Muhammadiyah University, North Sumatra - Wahyuni, Sri Fitri; Radiman, Radiman; Nanda, Ariska Ayu (Journal of International Conference Proceedings, 2023)
This study aims to examine the influence of love of money, peer groups, and financial literacy on the personal financial management of students enrolled in the Management Study Program at Muhammadiyah University, North Sumatra. This study employed survey research methods to collect data. Participants are chosen based on specific demographic criteria. This study employs a quantitative and correlational methodology, with data being gathered via questionnaires. The Slovin algorithm was utilized to select a sample from the class of 2018 at Stambuk University, consisting of 84 students who are currently enrolled in the Management Study Program within the Faculty of Economics and Business at Muhammadiyah University in North Sumatra. This research utilizes various statistical tests, including the classical assumption test, multiple linear regression, t test, F test, and coefficient of determination. The data was analyzed using SPSS 25. This study demonstrates that individuals who possess a strong desire for wealth experience positive outcomes in terms of their personal financial management. This study examines the impact of peer groups on individuals’ financial management practices. A significant and meaningful correlation was discovered. The findings indicate a significant and positive correlation between the variables.